Micronutrient supplement intakes among collegiate and masters athletes: A cross-sectional study - Nichols, Quentin Z.; Ramadoss, Rohit; Stanzione, Joseph R.; Volpe, Stella L. (Frontiers in Sports and Active Living, 2023)
Objective: In our cross-sectional study, we evaluated micronutrient supplementation intake among Collegiate and Masters Athletes. Methods: We conducted a cross-sectional study on female and male Collegiate and Masters Athletes. Micronutrient dietary and supplement consumption data were measured using a Food Frequency Questionnaire. A one-way analysis of variance was used to compare the following micronutrient dietary and supplement intakes: Vitamins A, B6, B12, C, E, D, and folate, niacin, riboflavin, thiamine, iron, magnesium, selenium, and zinc. When significant differences were found, a Tukey HSD post hoc test was performed to identify specific group differences. The significance level was set a priori at p<0.05. Results: A total of 277 athletes (134 women and 143 men) were included in the study. Participants were 35.85±11.1 years of age. The average height of all athletes combined was 171.42±9.68 cm. The average weight of all athletes combined was 72.90±14.23 kg. Body mass index (BMI) for all athletes combined was 24.68±3.65 kg/m2. The athlete population consisted of General Athletes (n=60), Runners (n=90), Triathletes (n=43), Rowers (n=34), CrossFit athletes (n=21), Cyclists (n=11), Resistance Training Athletes (n=11), and Powerlifters (n=7). Rowers had significantly greater vitamin E supplement intakes compared to Triathletes (13.37±4.20 vs. 3.71±5.59 mg/day, respectively) (p=0.025). Powerlifters (32.95±22.24 mg/day) had a significantly greater zinc intake compared to General Athletes (7.19±8.37 mg/day), Runners (7.35±11.34 mg/day), Triathletes (5.50±11.14 mg/day), CrossFit Athletes (12.68±22.72 mg/day) and Rowers (7.92±10.37 mg/day) (p=<0.001). Women had significantly greater calcium intakes compared to men (250.87±386.96 vs.123.87±212.50 mg/day, respectively) (p=<0.001). There were no other significant differences among the other micronutrient dietary and supplement intakes among the athlete groups or genders. Conclusion: Based on our data, Rowers had greater vitamin E supplement intakes compared to Triathletes. Powerlifters had greater zinc supplement intakes compared to General Athletes, Runners, Triathletes, CrossFit Athletes, and Rowers. Women had significantly greater calcium supplement intake compared to men. Further research is needed to continue evaluating dietary and supplement intakes among different types of Collegiate and Masters Athletes. Collegiate and Masters Athletes should consult qualified nutrition professionals about supplement use.